Sejarah Pemikiran Ekonomi Islam pada Masa Rosulullah SAW - Billi Jenawi; Devani Tarigan; Muhammad Daffa Prasetya; Ahmad Wahyudi Zein (STIKes Ibnu Sina Ajibarang, 2025)
Economic systems based on the principles of Islamic teachings from the Quran and Hadith are discussed in this article, which pertains to the period of the Prophet Muhammad and Islamic philosophy. Learning Islamic economics is a step toward creating a more moral society. The economic structure was changed so that everyone may gain, and the Prophet Muhammad was a major player in this. It was not overnight that the present application of Islamic economics emerged; rather, it evolved over time. The main challenge is to find historical traces that explain these developments, so that Islamic economic concepts can be understood and applied in sharia economic practices, which often receive little attention from historians.